Let 'er buck! : George Fletcher, the people's champion - Nelson, Vaunda Micheaux (Carolrhoda Books, 2019)
"African American George Fletcher loved horses from an early age. When he unfairly lost the 1911 Pendleton Round-Up to a white man, the outraged audience declared him "people's champion"--Provided by publisher.